2012
DOI: 10.1073/pnas.1212056109
|View full text |Cite
|
Sign up to set email alerts
|

Muscle synergy patterns as physiological markers of motor cortical damage

Abstract: The experimental findings herein reported are aimed at gaining a perspective on the complex neural events that follow lesions of the motor cortical areas. Cortical damage, whether by trauma or stroke, interferes with the flow of descending signals to the modular interneuronal structures of the spinal cord. These spinal modules subserve normal motor behaviors by activating groups of muscles as individual units (muscle synergies). Damage to the motor cortical areas disrupts the orchestration of the modules, resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

48
594
7
4

Year Published

2013
2013
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 529 publications
(677 citation statements)
references
References 21 publications
48
594
7
4
Order By: Relevance
“…His pattern was very similar to a recently studied cohort of stroke subjects, where newly formed abnormal synergies were also observed 6. However, another study found that synergies in the affected arm of severely impaired patients could be derived by merging and fractionation of synergies calculated in the unaffected upper‐limb, that is, new synergies were not evident 5. A possible reason for differences may be the neuroanatomical site of the lesion; stroke subjects with intact sensorimotor cortex have been found to have less similar synergies relative to the unaffected limb 16.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…His pattern was very similar to a recently studied cohort of stroke subjects, where newly formed abnormal synergies were also observed 6. However, another study found that synergies in the affected arm of severely impaired patients could be derived by merging and fractionation of synergies calculated in the unaffected upper‐limb, that is, new synergies were not evident 5. A possible reason for differences may be the neuroanatomical site of the lesion; stroke subjects with intact sensorimotor cortex have been found to have less similar synergies relative to the unaffected limb 16.…”
Section: Discussionsupporting
confidence: 87%
“…These synergies can be measured by creating lower dimensional representations of electromyography (EMG) signals. After stroke, however, there is a distinct change in the modular recruitment of muscles, thus resulting in abnormal synergies in the most impaired subjects 4, 5, 6. While the neural basis of such abnormal synergies is poorly understood, a commonly held view is that descending cortical inputs can shape subcortical circuits to organize and dynamically control the weighting of synergies 7.…”
Section: Introductionmentioning
confidence: 99%
“…A flexible temporal recruitment of motor primitives, as well as a flexible modification of the motor modules within each element, is used to achieve stable locomotion adapted to the mechanical demand during walking. Although there are several studies investigating clinical outcomes using the muscle synergies concept in the diagnosis and rehabilitation of pathologies, for example, in stroke (Cheung et al, 2012) and Parkinson's disease (Falaki et al, 2016), a direct translation to training and rehabilitation procedures is still limited. In the future, a better understanding of neuromuscular mechanisms through the analysis of muscle synergies may help to reliably identify motor control strategies, which is essential to improve the specificity of training and rehabilitation protocols in healthy and pathological population.…”
Section: Resultsmentioning
confidence: 99%
“…Cheung (Cheung et al, 2012) has outlined three possible strategies of change in muscle synergies after stroke.…”
Section: 5neuropathologymentioning
confidence: 99%